Clinical significance of stratifying prostate cancer patients through specific circulating genes - Seta Derderian; Edouard Jarry; Arynne Santos; Quentin Vesval; Lucie Hamel; Rafael Sanchez‐Salas; Alexis Rompré‐Brodeur; Wassim Kassouf; Raghu Rajan; Fadi Brimo; Marie Duclos; Armen Aprikian; et al. (Molecular Oncology)
Patient stratification remains a challenge for optimal treatment of prostate cancer (PCa). This clinical heterogeneity implies intra‐tumoural heterogeneity, with different prostate epithelial cell subtypes not all targeted by current treatments. We reported that such cell subtypes are traceable in liquid biopsies through representative transcripts. Expanding on this concept, we included 57 genes representing cell subtypes, drug targets and relevant to resistance as non‐invasive biomarkers for stratification. This panel was tested by RT‐qPCR (quantitative reverse transcription polymerase chain reaction) in blood of controls and different categories of PCa patients. Overall, circulating transcripts showed predictive value throughout the disease. Those with aggressive pathological features such as intra‐ductal carcinoma at diagnosis showed more genes over‐expressed. In metastatic patients, signatures of subtypes or resistance were associated with treatments, progression‐free survival and overall survival. Altogether, testing markers of cell diversity, an intrinsic feature of tumours, and drug targets via liquid biopsies represents a valuable means to stratify patients and predict responses to current or new therapeutic modalities. Over‐expressed drug target genes suggest potential benefit from targeted treatments, justifying new clinical trials to offer patient‐tailored strategies to eventually impact on PCa mortality.